The brain-specific upregulation of CARD11 in response to avian brain-neurotropic virus infection serves as a potential biomarker - Wenbin Wang; Yajie Zhang; Sa Xiao; Xuelan Liu; Peipei Yan; Chunyan Fu; Zengqi Yang (Poultry Science, 2023)
ABSTRACT: Avian neurotropic viruses are critical problems in poultry industry causing severe central nervous system (CNS) damage with neuroinvasive and neurovirulence properties. Biomarker of neurotropic viral intracranial invasion is of great application value for the diagnosis, but that of avian neurotropic viruses remains elusive. Previously, we found that chicken caspase recruitment domain family, member 11 (CARD11) was only upregulated in virulent Newcastle disease virus-infected chickens and in chicken primary neuronal cells. In this study, CARD11 was systemically expressed in chickens and pigeons detected by absolute qPCR and immunohistochemical (IHC) assay. After virus challenging, only avian neurotropic viruses (avian encephalomyelitis virus [AEV] and pigeon paramyxovirus type 1 [PPMV-1]) except Marek's disease virus (MDV) can invade brain and cause pathological changes. The relative mRNA expression of CARD11 was brain-upregulated in AEV- or PPMV-1-infected animals, rather than MDV and non-neurotropic viruses (fowl adenovirus serotype 4 [FAdV-4] and infectious bronchitis virus [IBV]). Similarly, the protein expression of CARD11 was only upregulated in the cerebra and cerebella infected by avian brain-neurotropic virus using IHC assay. And there were no correlations between the change level of CARD11 and viral load. Our preliminary data suggested that avian CARD11 may be a potential brain biomarker for avian brain-neurotropic virus invasion.